2014
DOI: 10.1186/1756-0500-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin 1 as a serum marker for breast cancer and its use in combination with CEA or CA15-3 for improving the sensitivity of breast cancer diagnoses

Abstract: BackgroundThe human cytosolic thioredoxin (Trx) contains a redox-active dithiol moiety in its conserved active-site sequence. Activation by a wide variety of stimuli leads to secretion of this cytoplasmic protein. Function of Trx1 has been implicated in regulating cell proliferation, differentiation, and apoptosis. The aim of this study was to assess the clinical significance of serum Trx1 level in patients with breast carcinoma.ResultsTo clarify whether serum levels of Trx1 could be a serum marker for breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Trx-1 stimulates MMP-9 expression and promotes MMP-9 dependent invasion in breast cancer cells [12]. Thioredoxin system is highly expressed in breast tumors [23,24] and Trx-1 has been previously suggested as a suitable and diagnostic biomarker for breast cancer [8,13]. Our results extend these previous studies to show that Trx-1 level is significantly increased in breast cancer patients as compared to control.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Trx-1 stimulates MMP-9 expression and promotes MMP-9 dependent invasion in breast cancer cells [12]. Thioredoxin system is highly expressed in breast tumors [23,24] and Trx-1 has been previously suggested as a suitable and diagnostic biomarker for breast cancer [8,13]. Our results extend these previous studies to show that Trx-1 level is significantly increased in breast cancer patients as compared to control.…”
Section: Discussionsupporting
confidence: 85%
“…One of the most important antioxidants is thioredoxin-1 (Trx-1), which is highly expressed in many tumors. A recent study showed increased level of serum Trx-1 in breast cancer patients in comparison with other cancers and normal persons [8]. Cellular redox homeostasis mediated by Trx-1 is required for activation of ribonucleotide reductase [9] and peroxiredoxins [10], induction of vascular endothelial growth factor (VEGF) and matrix metalloproteinase-9 (MMP-9) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…estimated the serum levels of thioredoxin1 (Trx1) in breast cancer patients using ELISA and confirmed its significantly elevated levels with high diagnostic sensitivity and specificity in GI samples. They also suggest that Trx1 combined with CEA and CA15‐3 significantly improved the sensitivity for the early detection of breast cancer with respect to grade . A study by Garczyk et al.…”
Section: Introductionmentioning
confidence: 92%
“…hioredoxin-1 (TRX-1) is a low molecular weight redox protein found in both prokaryotic and eukaryotic cells 1. It activates specific nuclear transcription factors involved in gene decoding for production of substances that protect cells from oxidative stress induced by free oxygen radicals 2 . It has been proposed that serum TRX-1 may be a useful biomarker for early prediction of breast cancer, and higher levels have been found in sera of breast cancer patients 3 . An increase in the level of TRX-1 has been found to be associated with decreased T 20 https://doi.org/10.31386/dmj.2017.11.2.3…”
mentioning
confidence: 99%